2014
DOI: 10.1016/j.bjane.2013.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of anaesthesiologists in Recife with respect to potential risks in the operating room—cross-sectional study

Abstract: educational campaigns should be implemented to improve the knowledge of health professionals and clarify institutions and professionals' rights and duties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A comprehensive literature is available on the health hazards in the healthcare industry. Although health care is supposed to be a safe practice [4], these professionals are exposed to various occupational hazards (e.g., infectious diseases) [5], which threaten their health and safety [6]. Several hospital studies have reported operating rooms to be a fundamental unit associated with the challenge of various physical, chemical, biological (e.g., infectious agents), ergonomic, and psychological hazards (e.g., stress and depression), as well as fire, explosion, electricity, and falls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive literature is available on the health hazards in the healthcare industry. Although health care is supposed to be a safe practice [4], these professionals are exposed to various occupational hazards (e.g., infectious diseases) [5], which threaten their health and safety [6]. Several hospital studies have reported operating rooms to be a fundamental unit associated with the challenge of various physical, chemical, biological (e.g., infectious agents), ergonomic, and psychological hazards (e.g., stress and depression), as well as fire, explosion, electricity, and falls.…”
Section: Introductionmentioning
confidence: 99%
“…However, occupational hazards cause extensive damage to these organizations, such as the loss of experienced workforce and adverse effects on patient safety [4,[7][8].…”
Section: Introductionmentioning
confidence: 99%